Comparative Analysis of Poly(N-methylpyrrole) and Its Titanium Dioxide Nanocomposite Film Formations Against Equivalent Electrical Circuit Model for The Their Corrosion-Inhibition Effects - Ateş, Murat; Kamer, Levent; Özkan, Haydar (SAGE, 2015)
Conducting polymers have been used for many years as coating materials against corrosion. However, the coated materials absorb water over time resulting in reduction of resistivity and anticorrosion properties. In this study, poly(Nmethylpyrrole) (P(N-MPy)) and P(N-MPy)/titanium dioxide ((TiO2) nanocomposite films were synthesized in 0.5 M oxalic acid solution on Al 1050 electrode by chronoamperometric method. The modified electrodes were characterized by scanning electron microscopy–energy dispersive X-ray analysis, Fourier transform infrared–attenuated transmission reflectance, electrochemical impedance spectroscopy (EIS), and Tafel extrapolation techniques. The corrosion tests results were obtained in 3.5% sodium chloride (NaCl) solution by Tafel plots. In addition, the equivalent electrical circuit model of P(N-MPy) and P(N-MPy)/TiO2 nanocomposite films were investigated in 3.5% NaCl solution at different time periods. The EIS study of the polymer and nanocomposite were analyzed by Matlab program and for the first time Tina, the equivalent electrical circuits program, was used.
Keywords: Corrosion; Electrical Circuit Mode; Poly(N-methylpyrrole); TiO2; Surface Coating; Al 1050